False Reporting and Its Impact on Public Employees - Al-Qara Ghuli, Ziad (Journal of Legal Sciences, 2026)
False reporting can have legal, professional, and moral repercussions for public employees, as it may expose them to administrative or criminal investigations, with the accompanying effects on their professional reputation and social standing. It may also disrupt the work of oversight and judicial bodies by occupying them with reports that are not based on true facts, which may hinder their efforts to combat real crimes, especially administrative and financial corruption. Conversely, restricting the right to report may lead to individuals refraining from reporting administrative and criminal crimes and violations, which may negatively affect efforts to combat corruption and promote integrity within state institutions. The legislator seeks to achieve a delicate balance between protecting public employees from malicious reports and encouraging individuals to report crimes and violations by criminalizing false reporting and imposing liability on those who deliberately submit false reports with the intent to harm others, while maintaining legal protection for whistleblowers who act in good faith and aim to uncover crimes or violations.